China's belt and road initiatives and its neighboring diplomacy - Zhang, Jie (World Scientific Pub., 2017)
This book studies China's Belt and Road Initiatives and the country's neighboring diplomacy. The Belt and Road Initiatives proposed by Chinese President Xi Jinping in 2013 consist of two main components, the land-based 'Silk Road Economic Belt' and ocean-going 'Maritime Silk Road'. China has implemented the initiatives by establishing Asian Infrastructure Investment Bank and Silk Road Fund. This book focuses on analysis of the initiatives and the responses from the major powers, neighboring countries and regions.